2019
DOI: 10.36067/jbis.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Do female commissioners have higher social responsibility? Research in manufacturing companies in Indonesia

Abstract: This study aims to test the slack resources and feminism of the board on the quality of corporate social responsibility disclosure. The population of this study is all companies listed on the Indonesian Stock Exchange during the 2014-2016 period. The data are collected by using the official IDX website. From this research, there were 539 companies listed in 2016, 525 companies listed in 2015 and 498 companies listed in 2014. This research consists of 75 companies that published a sustainability report. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The supervisory process will be more responsive to investors, increase the company's compliance with disclosures, and ultimately improve the disclosure quality. The board of commissioners supervises the administration and gives detailed information to be presented in the annual report (Fahmi & Adhivina, 2019). The woman has leadership qualities and has become a new paradigm of leader to modify feminine leadership with classical male traits (Book, 2009).…”
Section: Ha₁: Environmental Performance Has a Positive Effect On Corp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The supervisory process will be more responsive to investors, increase the company's compliance with disclosures, and ultimately improve the disclosure quality. The board of commissioners supervises the administration and gives detailed information to be presented in the annual report (Fahmi & Adhivina, 2019). The woman has leadership qualities and has become a new paradigm of leader to modify feminine leadership with classical male traits (Book, 2009).…”
Section: Ha₁: Environmental Performance Has a Positive Effect On Corp...mentioning
confidence: 99%
“…Meanwhile, Darma (2019) and Handayani & Maharani (2019)'s research found that environmental performance does not affect corporate environmental disclosure. In addition, research that has been conducted in proving the influence of the board of commissioners on the corporate environmental disclosure has varied results, where Fahmi & Adhivina (2019) and Dyah & Isnalita (2019) found that the female board of commissioners has a negative effect on corporate environmental disclosure. On the other hand, in Yusuf et al (2017) and Setiawan et al (2018), female commissioners positively affect corporate environmental disclosure.…”
Section: Introductionmentioning
confidence: 99%